Natural and artificially-induced habitat complexity and freshwater fish species composition - Freitas, CEC; Petrere, M.; Barrella, W. (Blackwell Publishing, 2005)
The effects of habitat complexity, induced by construction of artificial reefs, on the fish assemblages in the Barra Bonita reservoir, Brazil, and in the lotic zone immediately below the dam were studied. Four artificial reefs were constructed in each habitat at variable distances from the shore. Multiple correspondence analysis showed that the factors distance from the shore and type of habitat were determinants for the group formation, and artificial reefs had a lesser effect. Fish species composition was about the same at locations with and without reefs.
Keywords: artificial reefs; Brazil; fish assemblages; spatial distribution; Tiete River